Letter from Arnold O. Beckman to S. S. Prentiss - Beckman, Arnold O. (1945)
In this letter, Beckman discusses the testing and production of various models of the Pauling oxygen meter. Model F is discussed in the most detail, but Models P, G, and a damaged aircraft Model L are also mentioned. Developed from a Linus Pauling design during WWII, the technology behind Beckman Instruments’ oxygen analyzers ended up doing such diverse jobs as monitoring astronauts’ respiration, maintaining packaged food safety, and preventing blindness in newborn babies.
Keywords: Scientific apparatus and instruments; Oxygen--Measurement; Oxygen--Analysis; Linde Air Products Company; Beckman Instruments, Inc.